The Intersection of Law and Ethics – at 600 Grant Street, Pittsburgh, PA: Is it Ethical to Assert a Legal Technicality to Avoid Liability for a Debt Created by Fraud? - Cameron, George D. (Journal of business ethics, 2004)
A considerable literature exists regard-ing the moral obligation to keep one's promises. Several authors have focused on the exceptional circumstances which may or should excuse this moral duty. Less frequently discussed is the question of how this general moral obligation and its possible exceptions play out in the context of negotiable written promises to pay money, i.e., so-called "commercial paper.", This paper focuses on the application of the legal rules governing commercial paper, and on the ethical implications involved in the application of those rules. More specifically, it asks whether the assertion of the technical doctrine known as "holder in due course," and the denial of that status in some cases, promotes ethical behavior in the marketplace. By examining the circumstances of one case, involving a substantial investment and a large bank, I hope to shed some light on how the legal and ethical rules do in fact "intersect."